220k views
0 votes
Find the 4th term in the sequencewith the following definition:a1 = 2an = (an-1)2

Find the 4th term in the sequencewith the following definition:a1 = 2an = (an-1)2-example-1

1 Answer

4 votes

1)

In this sequence to find the 4th term, all we need is to plug the number into that Recursive Formula

so


\begin{gathered} a_1=2 \\ a_2=(a_(_1-1))^2=(2)^2=4 \\ a_{3\text{ }}=(a_2)^2=16 \\ a_4=(a_(4-1))^2=16^2=256 \end{gathered}

User IronKirby
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.